Growing Young Entrepreneurs: Does Social Support Affect Their Entrepreneurial Intention? - Luthfi Atin Khusna; Laila Listiana Ulya (Psikostudia : Jurnal Psikologi, 2024)
In the field of Industrial and Organizational Psychology, an individual's career choice to become an entrepreneur is an impressive topic to study, especially in the productive age, because entrepreneurship is one of the prerequisites for reaching developed notions and helps reduce the unemployment rate. Numerous efforts have been attempted to develop and facilitate an increase in the number of entrepreneurs among students. Unfortunately, with the various existing facilities and programs, students enthusiasm in the field of entrepreneurship is not invariably followed by the creation of a sustainable business. There is a contributing factor in entrepreneurial intentions, i.e., social support. Thus, this research aims to investigate the role of social support in entrepreneurial intentions among Semarang State University students who are actively involved in education or entrepreneurial activities (N=377) using a purposive sampling technique. This study collected data using 11 items on the entrepreneurial intention scale and 10 items on the social support scale. Simple linear regression was used to evaluate the data. The outcome demonstrates that social support plays a significant positive role in entrepreneurial intention, p < 0.05, R2 = 0.379 with the equation Y' = 26,748 + 0.600 X. This indicates that the higher social support score influences an individual to have the greater entrepreneurial intention. Therefore, It is also envisaged that the findings of this study would be useful to different parties when planning or creating acceleration program for the development of young entrepreneurs, particularly for those from collectivist cultures.Pada bidang Psikologi Industri dan Organisasi, pemilihan karier individu menjadi seorang wirausaha menjadi topik yang menarik untuk diteliti, terutama pada usia produktif. Hal tersebut disebabkan karena kewirausahaan merupakan salah satu prasyarat untuk mencapai negara maju dan membantu mengurangi tingkat pengangguran. Berbagai upaya telah dijalankan untuk mengembangkan dan memfasilitasi peningkatan jumlah wirausaha pada mahasiswa. Sayangnya, dengan berbagai fasilitas dan program yang ada, ketertarikan mahasiswa dalam bidang kewirausahaan tersebut tidak selalu diikuti dengan penciptaan bisnis yang berkelanjutan. Terdapat faktor yang dapat berperan dalam intensi berwirausaha adalah dukungan sosial. Oleh karena itu, Penelitian ini memiliki tujuan untuk menguji peranan dukungan sosial terhadap intensi berwirausaha pada mahasiswa Universitas Negeri Semarang yang memiliki keterlibatan aktif dalam pendidikan ataupun aktivitas kewirausahaan (N=377) dengan teknik purposive sampling. Data dikumpulkan menggunakan 11 item skala intensi berwirausaha dan 10 item skala dukungan sosial. Analisis data dalam penelitian ini menggunakan Regresi linier sederhana. Hasil penelitian menunjukkan dukungan sosial berperan positif terhadap intensi berwirausaha nilai p < 0,05, R2 = 0,379 dengan persamaan Y’ = 26.748 + 0,600 X. Hal tersebut mengartikan apabila terjadi peningkatan dukungan sosial maka akan semakin tinggi intensi berwirausaha. Dengan demikian, hasil penelitian ini diharapkan dapat menjadi pertimbangan berbagai pihak dalam menyusun ataupun mengembangkan program akselerasi penciptaan wirausaha muda, terutama pada individu dalam budaya kolektivis.